Use of Leptospira biflexa strains in the seroagglutination test for diagnosis of leptospirosis in sheeps and goats - Viegas, Edgard de Aquino; Yanaguita, Roberto Mitio; Viegas, Simone Assis Rosas de Aquino; Silva, Luzinete Alves; Vasconcellos, Silvio Arruda (Brazilian Journal of Veterinary Research and Animal Science, 1994)
Testing 13 serotypes of Leptospira biflexa as antigens, for the diagnosis of leptospirosis in sheeps and goats by means of the microscopic agglutination test, it was observed that the antigens jequitaia and buenos aires presented the best results. If for sheep sera there was no significant difference between the antigens jequitaia and buenos aires (0,70 < p < 0,50), for goat sera the jequitaia antigen was better than buenos aires (0.01 < p < 0.002). The occurence of some false positive results showed limitations in the specificity of the SAT with Leptospira biflexa strains as antigens.